Diversion's Application in The Juvenile Justice System to Realize Restorative Justice Related to Deprivation of Liberty Principle - Rofiq, Aunur (NORMA, 2020)
Diversion Efforts can only be carried out in cases of Children in conflict with laws that threaten their crimes under 7 (seven) years and do not constitute a repeat of a criminal act. In contrast, the juvenile justice system requires deprivation of liberty principle and punishment related to the latest findings. This research uses the normative legal research method, using the law method, research method, and comparative method. From this research, we know that diversion in the juvenile justice system cannot be done in every child's case; it can only be done in the case of children who meet the requirements of a case protected under 7 (seven) and not a repeat of follow up. Not all cases of children go through a process of diversion. Children who have a conflict with the law are directly threatened with criminal punishment. However, there has been a reconciliation between the perpetrators and the victims, so that the deprivation of liberty principle, and criminalization, is the latest result, which is not successful. Therefore, diversion shall not be used again to protect children.Keywords: Diversion, Children, Liberty